Structural insights into the competitive inhibition of the ATP-gated P2X receptor channel. Issue 1 (December 2017) - Kasuya, Go; Yamaura, Toshiaki; Ma, Xiao-Bo; Nakamura, Ryoki; Takemoto, Mizuki; Nagumo, Hiromitsu; Tanaka, Eiichi; Dohmae, Naoshi; Nakane, Takanori; Yu, Ye; Ishitani, Ryuichiro; Matsuzaki, Osamu; et al.
Abstract P2X receptors are non-selective cation channels gated by extracellular ATP, and the P2X7 receptor subtype plays a crucial role in the immune and nervous systems. Altered expression and dysfunctions of P2X7 receptors caused by genetic deletions, mutations, and polymorphic variations have been linked to various diseases, such as rheumatoid arthritis and hypertension. Despite the availability of crystal structures of P2X receptors, the mechanism of competitive antagonist action for P2X receptors remains controversial. Here, we determine the crystal structure of the chicken P2X7 receptor in complex with the competitive P2X antagonist, TNP-ATP. The structure reveals an expanded, incompletely activated conformation of the channel, and identified the unique recognition manner of TNP-ATP, which is distinct from that observed in the previously determined human P2X3 receptor structure. A structure-based computational analysis furnishes mechanistic insights into the TNP-ATP-dependent inhibition. Our work provides structural insights into the functional mechanism of the P2X competitive antagonist. P2X receptors are nonselective cation channels that are gated by extracellular ATP. Here the authors present the crystal structure of chicken P2X7 with its bound competitive antagonist TNP-ATP and give mechanistic insights into TNP-ATP dependent inhibition through further computational analysis and electrophysiology measurements.